PHYTOCHEMICAL PROFILE AND THERAPEUTIC VALUES OF PULP AND PEEL EXTRACTS OF Hylocereus undatus (Applied Biological Research, 2023)
The present study was aimed to examine the therapeutic values of  pulp and peel extracts of Hylocereus undatus by comparing the chemical compounds identified by using GC-MS. Antioxidant  activities were measured using DPPH●, ABTS●+, superoxide  radical, FRAP and phosphomolybdenum reduction assay.  Antidiabetic and anti-inflammatory activities were determined  using α-amylase inhibition method and heat induced hemolytic  technique. The results showed that both the extracts reduced the oxidative stress with pulp extract showing stronger antioxidant  activity. The antidiabetic and anti-inflammatory activities of pulp  extract were greater than peel extract with IC50 values of 222.97 and 16.56 µg mL-1, respectively. GC-MS analysis showed the  presence of phytosterols, steroids, triterpene, phenolic compounds  and esters of fatty acids. The study shows the presence of bioactive  compounds in H. undatus pulp and peel extracts with promising  health benefits.
Keywords: Antidiabetic; anti-inflammatory; antioxidant; Hylocereus undatus; oxidative stress